Multiple stimuli-responsive selenium-functionalized biodegradable starch-based hydrogels. Issue 6 (8th January 2018) - Sun, Tongbing; Zhu, Caizhen; Xu, Jian
Abstract : Biodegradable diselenide cross-linked starch-based hydrogels, composed of starch chain backbones with an enzyme hydrolysis property and selenium-containing cross-linkers with a redox responsive cleavage property, were synthesized via free radical copolymerization and used as stimuli-responsive drug release materials for biomedical applications. Abstract : Novel biodegradable diselenide cross-linked starch-based hydrogels were synthesized via free radical copolymerization, which serve as stimuli-responsive drug release materials composed of starch chain backbones with an enzyme hydrolysis property and selenium-containing cross-linkers with a redox responsive cleavage property. Rhodamine B (RB) loaded starch-based hydrogels were prepared in order to investigate their stimuli-responsive release behaviours. In the presence of external redox agents, the enzyme stimuli as well as the mixture of the above stimuli, the prepared starch-based hydrogels exhibit controlled multi-responsive release behavior of RB. Overall, the merits of good biodegradation and multi-stimuli responsiveness make these kinds of starch-based hydrogels promising biomedical candidates for the realization of controlled drug delivery.